An integrated marketing communication strategy to increase a number of inpathent visits at Efarina Etaham Hospital Berastagi - Zerry All Vindo Tarigan; Ali Napiah Nasution; Chrismis Novalinda Ginting (Jurnal Info Sains : Informatika dan Sains, 2024)
Health, as a human right, requires fair, equitable, and quality services for the entire community. The Indonesian government is committed to improving health by providing facilities, including hospitals. The Health Law emphasizes the right of every individual to access safe and affordable health care. Hospitals play a strategic role in improving public health, but have evolved into "business" institutions with a more focused approach. Modern healthcare requires a new paradigm, with hospitals actively engaged in marketing communication and promotion. Integrated Marketing Communication (IMC) becomes a crucial approach to achieving promotional goals and enhancing the hospital's publicity. Patient visit data at RS Efarina Etaham Berastagi for the period 2019-2021 shows fluctuations influenced by factors such as the COVID-19 pandemic. This study proposes the implementation of IMC at RS Efarina Etaham Berastagi, considering the characteristics of internal and external informants. The research method used is qualitative descriptive, combining in-depth interviews, observations, and secondary data analysis. The results indicate that RS Efarina Etaham Berastagi has implemented some elements of IMC, but there are still internal and external challenges to overcome. By strengthening IMC strategies, it is expected that RS Efarina Etaham Berastagi can be more effective in reaching the community, building a positive image, and increasing the number of inpatient visits. This research provides insights for hospital management and stakeholders to optimize marketing strategies to achieve better public health goals.